Career Concepts, Personality and Values of Some Canadian Workers: An Exploratory Study - Bourgeois, Robert-Paul; Wils, Thierry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
The purpose of this paper is to explore the underlying personality, dynamics, values and elements of job motivation which characterize workers identifying themselves to one of Driver's four career streams from three different perspectives i.e. career to date, probable career and ideal career.